EVALUASI KINERJA ANGGARAN DAERAH KABUPATEN SIDOARJO - Lestari, Lestari; Karyadi, Iman (Equilibrium: Jurnal Ekonomi-Manajemen-Akuntansi, 2014)
The purpose of this study are: to determine the effectiveness of the Sidoarjo regency Budget as seen from the Regional financial performance. The population in this study was planned and realized number of local budgets in Sidoarjo. The sample in this research is the realization of the budget plan and the district of Sidoarjo in 2008, 2009, 2010, 2011, and 2012. The data analysis technique used is the Qualitative Methods. The results showed that the analysis of trends in percentage (percentage trend analysis) Sidoarjo district budget growth has a tendency to rise from year to year. In addition, the ability of the local government district of Sidoarjo in maintaining and improving the success that has been achieved from period to period is good. Sidoarjo regency government in the last 5 years more mnegeluarkan immediate shopping for shopping facilities and equipment for the purposes of operational activities and to fund services.